PEMANFAATAN TIK DALAM MENUMBUHKAN KARAKTER RELIGIUS PESERTA DIDIK SEKOLAH DASAR DI GELUMBANG - Primasari, Dwi Ammelia Galuh; Maryani, Sri; Suparmanto, Suparmanto; Juwita, Diana (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
The influence of technological developments in the current era of globalization is something that is inevitable, including in the world of education. This study aims to describe the use of IT in an effort to develop religious character in elementary school students in Gelumbang. This research was conducted because of the importance of growing the religious character of children since elementary school. This study used a qualitative approach with observation techniques, and interviews with educators and students in 3 cluster schools in Gelumbang District. The results of the study show: (1) elementary schools in Gelumbang have used IT to support character education activities in schools, despite some limitations; (2) Educators and principals work together to instill and develop religious character in their learners through spiritual activities; and (3) through IT assistance, activities in developing religious character Students become more interesting and meaningful. This effort, is expected to form positive religious character, and build the closeness of learners and creators.